Strategic information suppression in borrowing and pre-lending cognition: Theory and evidence - Zhongwen Chen; Xiaojian Zhao (Games, 2023)
This paper theoretically studies the interaction between an informed borrower and an uninformed lender facing possible default of a loan application. The lender is motivated to invest cognitive resources before making a lending decision. If the regulatory fine is weak, it is impossible for a bad-debt borrower to fully disclose his situation in the application. In this case, when the likelihood of a bad debt is low, the borrower always claims that nothing in the application is wrong. Otherwise, the borrower randomizes between full disclosure and information suppression. The transaction cost of the lender's pre-lending cognition increases with the default probability, as the default probability is small and decreases thereafter. Evidence from a peer-to-peer lending platform with 816,274 observations between 2012 and 2015 in the United States is largely consistent with our model implications.
Keywords: D82; D83; D86; L14; L15; G51; 330; information suppression; cognition; motivated belief; awareness; P2P platforms